Pertanggungjawaban Pemilik Senjata Api Legal yang Disalahgunakan Oleh Orang Lain - Widiastuti Endah Febrianti; Jamiatur Robekha (Syntax Corporation, 2023)
This study aims to obtain information and analyze the law regarding the ownership of legal firearms that are misused by others. Using the approach method in this study is a normative juridical approach. The widespread spread of firearms among civilians is a global phenomenon. The lack of supervision of firearm ownership, both legal and illegal owned by the general public, police and TNI, is one of the causes of crimes with misuse of firearms in Indonesia. While the victims who died as a result of this crime were mostly civilians. In Indonesia, exact figures on the trade in firearms, legal or illegal, are difficult to obtain, although their circulation in civil society is certain to increase sharply. Due to the lack of order and supervision of firearm administration, police officers do not know for sure how many firearms are circulating in the community, making firearm ownership very difficult to trace. The circulation of firearms will certainly cause unrest in the community, considering that firearms are very dangerous. The use of firearms is legal alias licensed as owned by members of the police, TNI, agencies / agencies and the general public. But there are also illegal alias unlicensed, unlawful and very potentially used for crime. The use of legal firearms in practice is inseparable from various problems, in addition to unscrupulous officers who misuse their firearms, there are also people who have firearm permits who violate the rules, such as for criminal acts.